Effects of Shear Stress on Production of FVIII and vWF in a Cell-Based Therapeutic for Hemophilia A - Trevisan, Brady; Morsi, Alshaimaa; Aleman, Julio; Rodriguez, Martin; Shields, Jordan; Meares, Diane; Farland, Andrew M.; Doering, Christopher B.; Spencer, H. Trent; Atala, Anthony; Skardal, Aleks; Porada, Christopher D.; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Microfluidic technology enables recapitulation of organ-level physiology to answer pertinent questions regarding biological systems that otherwise would remain unanswered. We have previously reported on the development of a novel product consisting of human placental cells (PLC) engineered to overexpress a therapeutic factor VIII (FVIII) transgene, mcoET3 (PLC-mcoET3), to treat Hemophilia A. Here, microfluidic devices were manufactured to model the physiological shear stress in liver sinusoids, where infused PLC-mcoET3 are thought to lodge after administration, to help us predict the therapeutic outcome of this novel biological strategy. In addition to the therapeutic transgene, PLC-mcoET3 also constitutively produce endogenous FVIII and von Willebrand Factor (vWF), which plays a critical role in FVIII function, immunogenicity, stability, and clearance. While vWF is known to respond to flow by changing conformation, whether and how shear stress affects the production and secretion of vWF and FVIII has not been explored. We demonstrated that exposure of PLC-mcoET3 to physiological levels of shear stress present within the liver sinusoids significantly reduced mRNA levels and secreted FVIII and vWF when compared to static conditions. In contrast, mRNA for the vector-encoded mcoET3 was unaltered by flow. To determine the mechanism responsible for the observed decrease in FVIII and vWF mRNA, PCR arrays were performed to evaluate expression of genes involved in shear mechanosensing pathways. We found that flow conditions led to a significant increase in KLF2, which induces miRNAs that negatively regulate expression of FVIII and vWF, providing a mechanistic explanation for the reduced expression of these proteins in PLC under conditions of flow. In conclusion, microfluidic technology allowed us to unmask novel pathways by which endogenous FVIII and vWF are affected by shear stress, while demonstrating that expression of the therapeutic mcoET3 gene will be maintained in the gene-modified PLCs upon transplantation, irrespective of whether they engraft within sites that expose them to conditions of shear stress.